O estagiário futuro professor e o estágio não obrigatório na construção da formação docente - Carvalho, Natan Moraes de (2024)
This research intends to contribute to the discussion about the formation of interns, students of the undergraduate teacher education course of Pedagogy, investigating the formative potential of the non-mandatory internship offered by the Federal University of Piauí (UFPI) in a joint project with the Municipal Department of Education (SEMEC) of the city of Teresina-PI. The guiding questions of the research were: Which motivations lead the undergraduate students of Pedagogy to the non-mandatory internship? According to the interns, what are the knowledges built within the non mandatory internship in the schools of SEMEC (Municipal Department of Education and Culture)? How does the non-mandatory internship contribute for the professional formation? How do the interns describe the conduction of the educational practices and the pedagogical actions developed in the internship? What information do the guiding documents about the compulsory curricular internships and the non-mandatory internships bring? The main objective of the research is to identify which teaching knowledges the future teacher student affirms to build through the non-mandatory internship in the schools of SEMEC/Piauí. As for the specific objectives, we intend to know how the interns understand and express the alternance established between the theory (the university classes) and the practice (activities developed in the non mandatory internship); to identify the knowledge built during the non-mandatory internship, according to the interns themselves; and analyze the legal orientations about the internships in the undergraduate teacher education courses (the compulsory curricular and the non-mandatory internships). The hypotheses investigated are linked to the ideas that: a) the interns understand and express the importance of the internship for their formation and for the day by day knowledge of the profession, however they refer too little to the process of alternance between the theory (the university classes) and the practice (activities developed in the non-mandatory internship); and b) the knowledge built during the non-mandatory internship, according to the interns themselves, is directly linked to the practical situations lived and not to the conceptual reflections. This research has a qualitative nature, whose data was collected by means of questionnaires applied to a class of 17 senior students-interns, from the last period of the Pedagogy course, besides an individual interview and written narratives about the experiences of formation in the non-mandatory internship with four of these students. The research also used the documental analysis, focusing on the legislation and specific normative about the non-mandatory internship in the state of Piauí. The following authors provide theoretical support for the research: Tardif, Shulman, Pimenta, Anastasiou, Lucena Lima, Malglaive, Marcelo, Fazenda, Giesta, and Freire. The results partially confirmed the research hypothesis, determining that, although the interns reveal to understand the importance of the internship for their formation and for the day by day knowledge of the profession, how they refer to the process of alternance between the theory (the university classes) and the practice (activities developed in the non-mandatory internship) reveal a mechanist view of this relation, as if the theory were something to be mechanically applied to the practice. It seems that the interns do not realize that the teaching profession concerns a theoretical-practical field, in which the theoretical issues emerge from the practice and materialize. Yet, it is evident to the students-interns the contribution of the non mandatory internship for the development of the teacher formation and for the learning of the teaching profession